Simulation Of Magnetorheological Elastomer (Mre) Damping Mechanism - Zahari, Shahirah (Universiti Sains Malaysia, 2017)
Vibration is fundamental subjects in engineering. Severe problems may arise from vibration when material is not carefully selected for its dynamic integrity. The main aim of this project is to develop a better understanding about damping. There are three cases studied in this project which were the influence of material on damping mechanism, the influence of frequency on damping mechanism and the influence of force on damping mechanism. The effect of tan δ was analyzed for all cases. For the first case, natural rubber (NR), MRE #1 and MRE #2 were selected to investigate the influence of material on damping mechanism. Result obtained shows MRE #2 had excellent tan δ compared to NR and MRE #1. For the second case, five different frequencies, 20 Hz, 40 Hz, 60 Hz, 80 Hz and 100 Hz were selected in order to study the influence of frequency on damping mechanism. The data obtained shows that after 61 Hz, a rapid decrease of tan δ was observed. For the third case, five different forces of 0.5 N, 1.5 N, 2.5 N, 3.5 N and 4.5 N were selected to observe the influence of force on damping mechanism. The result shows the relationship between tan δ and force is approximately linear with the value of tan δ increase up to 0.2910. In addition, there is slight difference in values of simulation tan δ with experimental tan δ when compared. The value that was obtained from simulation tan δ for NR, MRE #1 and MRE #2 were 0.1225, 0.1473 and 0.1586 while for experimental tan δ were 0.1202, 0.1472 and 0.1584. The difference for the simulation tan δ compared with experimental tan δ was not exceed than 2% and in a good agreement.